Susceptibility of solanum phureja (juz. et buk.) to potato yellow vein virus (2010)
Sixty two virus-free accessions of Solanum phureja from the Colombiancentral collection of this tuber (Bogotá-Soacha) weretested for their susceptibility to infection with Potato yellowvein virus (PYVV). Under greenhouse conditions, the plantswere inoculated with PYVV using viruliferous Trialeurodesvaporariorum (Westwood) whiteflies, and monitored for threemonths (the tuber formation period of S. phureja) for symptomsof infection and virus capsid protein (CP) production, by meansof a reverse transcription-polymerase chain reaction (RT-PCR)assay. Symptoms of PYVV infection, consisting in the chloroticflecking of leaflets, followed by complete vein yellowing, werenoted in 38 accessions whose RNA extracts generated correctsizedCP amplicons in RT-PCR assays. Thirteen of the remainingaccessions were found to be latently infected with the virusthrough positive RT-PCR assays. Twelve accessions were freeof virus infection as judged by the absence of symptoms andnegative RT-PCR assay results over two cycles of tuber settingand germination. These accessions may possess field resistanceto PYVV. This work is the first one to detect and define the levelsof susceptibility of Colombian S. phureja accessions to PYVVinfection, and to identify the potential existence of resistanceto this deleterious Andean potato virus